Paramedic Practitioners within ambulance services: views of Australian policymakers, health professionals, and consumers - Matt Wilkinson-Stokes; Celene Y. L. Yap; Di Crellin; Ray Bange; George Braitberg; Marie Gerdtz (BMC Health Services Research)
Abstract Background Globally, ambulance services face overwhelming primary and urgent care presentations that they are not structurally or culturally designed to manage efficiently or effectively. One mechanism to meet this consumer demand is the implementation of Paramedic Practitioner models with postgraduate qualifications in primary and urgent care. This study explores interest-holder views on reactive Paramedic Practitioner models within Australian ambulance services. Methods A multidisciplinary team representing ambulance services was formed, including paramedicine, nursing, and medicine. A realist lens was adopted, and a qualitative research design using inductive thematic analysis employed. Semi-structured focus groups or interviews were conducted to obtain data from 56 participants. Interest-holders represented included consumers (n = 16), members of parliament (n = 3), government executives (n = 8), industry executives representing emergency medicine, general practice, nursing, and paramedicine (n = 6), ambulance service executives and medical directors (n = 7), researchers (n = 8), and practicing clinicians from paramedicine, nursing, and medicine (n = 8). Results Consumers described calling ambulance services for non-emergency complaints as they didn’t know if their concern was an emergency or not, not wanting to go to hospital, and wanting someone to listen to them, reassure them, and then quickly solve their problem on the spot: they saw Paramedic Practitioners as aptly meeting this need. Among the healthcare professions, opinions were divided. Most participants were largely unfamiliar with Paramedic Practitioners or the evidence base supporting this model of practice, the concept received widespread support at the clinician level, and a small but avidly dissenting contingent of national policymakers opposed the models. Paramedic Practitioner models were considered to require broad support across the healthcare system to be effective. Policymakers were unsure which outcomes they wanted measured to evaluate models. Conclusion This study reports a wide range of interest-holder perspectives on the use of reactive Paramedic Practitioners within Australian ambulance services. Enablers (n = 10) and barriers (n = 10) to efficient and effective Paramedic Practitioner models were identified. Key outcomes of interest (n = 6) were identified, and these may be operationalised in future evaluations of reactive Paramedic Practitioner programs.